Sehat Bersama Prolanis: Cegah Interaksi Obat pada Hipertensi dan Diabetes Melitus di UPTD. Puskesmas Lok Bahu Samarinda - Putri Anggreini; Ai Widiawati; Azzahra One Elaysandra; Lorenza Dwi Anggraini (Universitas Pahlawan Tuanku Tambusai, 2026)
Chronic Disease Management Program (Prolanis) patients, especially those with diabetes mellitus and hypertension, generally take several types of medication simultaneously. This condition can increase the risk of drug interactions that can potentially affect the patient's clinical condition. The purpose of this community service is to increase the knowledge and understanding of Prolanis patients regarding drug interactions in diabetes mellitus and hypertension therapy so that medication use is carried out safely and effectively. The method applied is health promotion through the distribution of leaflets and the delivery of educational materials using PowerPoint presentations. Assessment of participant understanding is carried out through the implementation of pre-tests and post-tests to measure changes in the level of knowledge after the educational activities are provided. The evaluation results show an increase in participant knowledge after the health promotion implementation. This is evident from the increase in the average score of participants. This is evident from the increase in the average score of participants in the understanding category from 0% in the pre-test to 77% in the post-test. The results indicate that health promotion based on education and information media can be an effective strategy to increase Prolanis patients' understanding regarding drug interactions.